1965
DOI: 10.1136/thx.20.5.469
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous Network of the Lung and its Change with Age

Abstract: The remarkable elastic behaviour of the lung entails both continuous tissue stress and a cyclic stress produced by the fluctuating difference between intrathoracic and intra-alveolar pressures throughout the entire span of life. In spite of these potentially disruptive forces, lung structure is preserved by the fibrous connective-tissue proteinscollagen, elastin, and reticulin. These extracellular proteins are characterized by their insolubility, resistance to destruction, and high tensile strength. Collagen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
2
1

Year Published

1972
1972
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(23 citation statements)
references
References 11 publications
1
19
2
1
Order By: Relevance
“…The fragility of collagenase-treated lungs prevented the investigation of changes occurring at high transpulmonary pressures in the present study. Consideration of the anatomical association of collagen and elastin in the lung has led to the view that collagen plays the major role in maintaining the structural integrity of the lung (13). In contrast, the present study suggests that major alterations in lung structure and elastic behavior are associated with alterations in elastin.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The fragility of collagenase-treated lungs prevented the investigation of changes occurring at high transpulmonary pressures in the present study. Consideration of the anatomical association of collagen and elastin in the lung has led to the view that collagen plays the major role in maintaining the structural integrity of the lung (13). In contrast, the present study suggests that major alterations in lung structure and elastic behavior are associated with alterations in elastin.…”
Section: Discussioncontrasting
confidence: 54%
“…From such studies it has been suggested that collagen is the major determinant of lung structure (13) and that elastin plays little role in lung elastic behavior (14). In contrast, the present study indicates that enzymatic attack of elastin is associated with marked architectural changes and altered elastic behavior of the lung.…”
Section: Introductioncontrasting
confidence: 47%
“…Consistent with this, the extensibility of elastin is much greater than collagen (22). Also, even though the uncoiling of these fibrous elements may affect lung elasticity more than their linear extension (3). lung compliance is increased after exposure to elastase but not collagenase (8).…”
Section: Discussionmentioning
confidence: 99%
“…The separate functions of these fibrous proteins have been deduced from histological studies of their arrangement in the lung parenchyma (1)(2)(3) and from the mechanical behavior of elastin and collagen fibers dissected out from other tissues (4,5). Further knowledge has been gained Received for publication 6 November 1974 and in revzised forni 6 February 1975. by studying the effects of elastolytic and collagenolytic enzymes on lung structure and function (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Once elastin is synthesized and stabilized by crosslinks, it does not undergo rates of turnover common to other proteins (10,23,28,97,(105)(106)(107)(108). For example, the data in Figure 8 indicate that the elastin in whole lung turns over very slowly.…”
Section: Turnover and Degradation Of Elastin In Lungmentioning
confidence: 99%